PSYCHOPHYSICAL CONDITION OF VISUALLY IMPAIRED STUDENTS DURING PHYSICAL EDUCATION CLASSES - Adyrkhaiev, S.G. (European Scientific Journal, ESJ, 2014)
This paper presentsthe results of author’s research, aimed to substantiate the dynamics of the parameters of psychophysical condition of visually impaired students during physical education classes while studyingin institutions of higher learning. Methods:The research was held on indicators of psychophysical condition such as power of neural processes, anxiety, mood, activeness, and the need for achievement. Results: It was proved that purposeful psychophysical development of visually impaired students under the influence of effective means, methods and forms of physical education that correspond to characteristics of the nosology and operational condition, provides full inclusion in the educational process of physical education inuniversities.